2014
DOI: 10.1097/bot.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Distal Ulna Fractures

Abstract: These results do not show any clear biomechanical advantage of locked plating for fractures of the distal ulna. The increased stiffness associated with locked plating likely contributes to earlier and more pronounced failure mechanisms under repetitive axial torsion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The loads in this study were selected to simulate extreme physiological loading such as lifting a heavy grocery bag with the forearm in a horizontal position. 18,20,21 Furthermore, these loads did not cause plastic deformation, as indicated by the complete recovery of motion after each iteration. Clearly, these loading conditions are beyond those experienced during healing of an ulna with rigid fixation; however, they were still valid for nondestructive cyclic loading.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The loads in this study were selected to simulate extreme physiological loading such as lifting a heavy grocery bag with the forearm in a horizontal position. 18,20,21 Furthermore, these loads did not cause plastic deformation, as indicated by the complete recovery of motion after each iteration. Clearly, these loading conditions are beyond those experienced during healing of an ulna with rigid fixation; however, they were still valid for nondestructive cyclic loading.…”
Section: Discussionmentioning
confidence: 94%
“…These observations suggested that a considerable stress concentration was applied at the distal-most screw following sagittal plane bending loads for 3.5-mm constructs. 18,44 In addition, none of the 2.7-mm constructs with a transverse fracture completely detached. Instead, the plate bent considerably, plastically deforming, and displaced the fracture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final destructive tests revealed that axial rotational loading in which the locked plate is constructed failed earlier than the nonlocked plates. 50 Therefore, based on the current evidence, both types of plates can be used in USO surgery without a preference for one over the other.…”
Section: Introductionmentioning
confidence: 99%